ANALISIS PENILAIAN TINGKAT TEKNOLOGI PADA GALANGAN KAPAL DI SEKITAR PPI MUARA ANGKE - Vita Rumanti Kurniawati (Institut Pertanian Bogor, 2011)
Muara Angke fishing port is one of fishing ports in DKI Jakarta which is dominated by small fishing vessels (less than 30 GT). In order to ensure safety at sea, those vessels require maintenance periodically. Consequently, shipyard which is located close to the port is the important industry to meet the demand of fishing vessels maintenance. Indirectly, shipyard’s adopted technology influence the quality of maintenance. The technology level assessments conducted by Fauzan et al. (2009) and Natapraja (2010) in two shipyards showed the technology contributions in those shipyards were classified at normal contribution and semi modern level with slight difference in TCC (0.447 compare to 0.415). Based on their results, the smaller shipyard had a bigger TCC than the larger one. Therefore, in this research, there will be analysed the causal factors of the differences. This is a descriptive comparative research and as the main object of research is the technology level assessment from two shipyards. The result showed the factors affecting the assessment were shipyard conditions, resource person’s reliability and different assessors’ perception. Moreover, it was noticeable that computerize gave a significant effect on shipyard’s technology level. Good knowledge in assessment’s criteria, either qualitative or quantitative may determine the accuracy of assessment’s result.